Korelasi Prilaku Personal Hyegiene Saat Menstruasi dengan pH Vagina pada Mahasiswi di Asrama UMPRI - cynthia puspariny (LPPM Universitas Respati Indonesia, 2021)
Personal hygiene in menstruation is also very important because it can trigger vaginal discharge. Leucorrhoea usually occurs due to unbalanced vagina PH (hydrogen potential). Inappropriate personal hygiene behavior in menstruation is not only done by teenagers who do not understand reproductive health, but health students have less personal hygiene behavior. The purpose of this study was to determine the correlation of personal hyegiene behavior during menstruation with Genetalia pH in Health Students. The research used is descriptive correlation with cross sectional design using purposive sampling of 82 samples conducted in July - September 2019 at the Muhammadiyah Pringsewu University Dermatory. Research Results The majority of personal hygiene behavior is sufficient for 44 respondents (53.7%), genetalia pH is mostly normal as many as 50 respondents (61%) and the results of the Spearman rho correlation test obtained a p value of 0.000. Based on these results, the importance of education on personal hygiene during menstruation is carried out before or immediately after menstruation for young women and the importance of providing repeated education on personal hygiene for adolescents living in dormitories.